Wind and Wave Hybrid Renewable Energy System - Kunasegaran, Lashvindraen; Mad Sahar, Nan (Evolution in Electrical and Electronic Engineering, 2022)
TThe aim of this study is to generate electricity using hybrid renewable energy, which is wind energy and wave energy, to design and build a smaller-scale hybrid wind turbine and wave energy converter to generate electricity using sea breeze and wave and to measure the efficiency of the proposed tool in harvesting renewable energy. The data that has been obtained from this project is the measured output voltage from the wing turbine and wave paddle, as well as the measurement of total output voltage after combining both voltages in series. The data were obtained over the period of 3 days at Air Papan Beach, Mersing. The highest recorded wind turbine output voltage is 9.3V at a forecasted wind speed of 13 km/h. The range of output voltage from wave energy is 0–4.4V. The range of total output voltage is 0 –6V because of the voltage regulator LM7806 in the power circuit that regulates 6V DC voltage for the convenience of a rechargeable battery. In conclusion, we can produce power using renewable energy sources like wind and waves from the ocean. Gathering both renewable sources of energy under one platform, would not only be more cost-effective but would also reduce the strain on the building’s infrastructure and workload. The constructed system’s efficiency can be seen in the project’s output because, by connecting the voltages in series, the system creates a load voltage equal to the total of both output voltages. This demonstrates an improvement in the efficiency of the produced output voltage. The loss of voltage or fluctuation caused by neither of the prime movers when there is no wind or wave can also be counterbalanced or smoothed by the capacitor.